Uso da cromatografia gasosa para avaliação da difusão em membrana de polietileno De Alta Densidade (PEAD) em contato com hidrocarboneto - Valentin, Clever Aparecido; De Souza Bueno, Benedito; Lodi, Paulo César [UNESP] (My University, 2012)
The constant petrol fuel leak in gas stations has caused concern in many countries around the world. Those fuels have toxic organic compounds in their composition, like Polycyclic Aromatic Hydrocarbons (PAH), which are harmful to the human health. In this work the efficiency of the protection layer with a High Density Polyethylene (HDPE) membrane of 2.5 mm thickness was evaluated. The study was based in the diffusive process in the intact membrane by a permeameter developed to evaluate the diffusive process. The membrane was putted in the middle of the system to separate two sides: a local soil impregnated with diesel oil (in one side) and pure water (in the other side). The chromatography technique was conducted to evaluate the contamination in the pure water. The analyses were made monthly in a total period of 6 months of research. The results tests show that the membrane was less effective to antracene and naphthalene compounds. Despite that, the results showed that the HDPE membrane is a good alternative to prevent contamination of water and soil by the compounds under study up to one year, based on the performance in the time of study.
Use of gas chromatography for the evaluation of the diffusion in High Density PolyEthylene (HDPE) membrane in contact with hydrocarbon
Keywords: Diffusion; Gas chromatography; Hydrocarbons